Destination Rejuvenation Strategy, Digital Engagement on Millennial Generation Loyalty with Place Attachment as a Mediating Variable Case Study in Senggigi, Lombok - Syamsul Ramdhani; Muhammad Mujahid Dakwah (LP2M IAIN Palopo, 2025)
This study investigates the mediating role of place attachment between destination rejuvenation strategy and digital engagement on millennial tourist loyalty at Senggigi, Lombok. Employing quantitative explanatory research design, 150 millennial tourists aged 25-40 with prior Senggigi experience were selected through purposive sampling. Data were collected via online questionnaire utilizing five-point Likert scale measuring destination rejuvenation strategy, digital engagement, place attachment, and millennial tourist loyalty. PLS-SEM with SmartPLS 3.0 software analyzed the structural relationships using bootstrapping procedure with 5,000 samples. Results demonstrate that digital engagement exerts an extraordinarily strong direct effect on place attachment (β=0.940, p<0.001), while place attachment substantially influences millennial tourist loyalty (β=0.710, p<0.001). Direct effects from destination rejuvenation strategy and digital engagement on loyalty were rejected, indicating place attachment functions as a critical mediating mechanism. Findings substantiate emotion-based loyalty frameworks, demonstrating that psychological attachment rather than tangible facility improvements drives loyalty manifestations. These findings advance theoretical understanding of destination marketing effectiveness through attachment cultivation mechanisms and provide practical guidance for destination managers prioritizing digital engagement quality and authentic community connection cultivation as primary loyalty determinants.